Negotiating the Continuity of Blangikhan: An AGIL Analysis of Institutional, Customary, Religious, and Community Roles in Negeri Olok Gading - Sheila Andini Putri; Ahmad Zarkasi; Luthfi Salim; Muslimin Muslimin (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
The continuity of local religious traditions depends on relationships among community authorities, public institutions, and residents, yet previous studies have often examined these actors separately. This study analyzes how social functions are distributed among the actors involved in Blangikhan, a pre-Ramadan purification tradition in Negeri Olok Gading, Bandar Lampung, and how they negotiate public promotion, religious interpretation, youth participation, and value transmission. A qualitative approach with a sociological orientation was employed. Data were collected in 2026 through nonparticipant observation, document review, and in-depth interviews with six purposively selected informants: one Tourism Office representative, one customary leader, one religious leader, and three community members. The data were coded using Parsons’s AGIL framework and compared through source triangulation. The findings indicate that the Tourism Office primarily supported adaptation through facilitation and promotion, religious leadership contributed to the formulation of legitimate purposes, community participation supported integration, and customary leadership maintained inherited patterns. These functions nevertheless overlapped and were produced through coordination rather than a fixed division of responsibilities. The actors negotiated continuity by retaining customary control over ritual procedures, evaluating practices through Islamic principles, involving residents in collective preparation, and explaining ritual meanings to younger participants. Public promotion through festivals and digital media was intended to extend visibility but also introduced concerns about cultural display and commercialization, while education and employment mobility complicated regular youth participation. The study shows that AGIL is useful for mapping interdependence when it is applied without assuming complete consensus or stable equilibrium.